2015
DOI: 10.5455/2349-3933.ijam20150516
|View full text |Cite
|
Sign up to set email alerts
|

Awareness rate of Ardabil city people about multiple sclerosis

Abstract: Background: Multiple Sclerosis (MS) is a chronic autoimmune disease of the central nervous system (brain and spinal cord) and affects the optic nerves. The aim of this study was to evaluate the knowledge rate of Ardabil city people about multiple sclerosis. Methods: This study is a descriptive analytical study that has been done on 150 people of Ardabil which selected randomly from all over the city based on geographical location. Data gathered by a questionnaire include two section characterized and knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A study conducted in Iran showed the insignificant contribution of media to providing education about MS [ 46 ]. Two other studies also found poor public knowledge about MS and argued that mass media were a suitable route for improving public knowledge about MS [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Iran showed the insignificant contribution of media to providing education about MS [ 46 ]. Two other studies also found poor public knowledge about MS and argued that mass media were a suitable route for improving public knowledge about MS [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant relationship between education level and knowledge and there was no significant relationship between employee status, education with knowledge level. 16 The most source of women about MS was friends and acquaintances, Awareness of patients and their friends and relatives about the disease can play an important role in controlling the disease because knowledge and awareness of relatives of patients who are the main careers of patients, can have an appropriate response to worry, fatigue, irritability and other patient behaviors. In the present study women's awareness nature of non-communicable of MS disease was 62.7% which was lower than some internal studies such as Amani et al with 88% awareness.…”
Section: Discussionmentioning
confidence: 99%
“…If people do not have enough information about the disease they will prevent them from getting close to them and thus increase their depression and anxiety in MS patients. 16 MS is one of the chronic diseases of the central nervous system due to its high incidence at young age leads to a reduction in individual and social efficiency. Most of MS patients are in second or fourth decades of life that this age range is a person's effectiveness period.…”
Section: Discussionmentioning
confidence: 99%